Antígeno prostático libre y total en pacientes de 40 a 70 años que acuden a consulta externa en el Hospital General Isidro Ayora de la ciudad de Loja - Jumbo Solano, Dayra Vanesa (2016)
The male population from age 50 is more likely to get prostate cancer, a tumor that occupies the third cause of death in male patients, in which the “age” is a risk factor to develop it. This is the reason why we recommend the free and total PSA test from the 40 years for early diagnosis. That is why in this study we proposed to quantify serum levels of free and total PSA in patients 40 to 70 years, we classify the values of the Free and Total PSA by age groups and identify the type of alteration by the prostate values obtained from free and total PSA attending outpatient clinic at the Isidro Ayora Hospital in Loja city. This study is descriptive and cross section with a sample of 90 patients who had the inclusion criteria. Fieldwork was conducted in the period from march to may 2015, automated electrochemiluminescence method was applied. After getting the information; the following results were obtained: 38.89% of the patients had serum 4.1-10 ng/ml (nonspecific prostatic disease), with values of 3.33% 10.1-20 ng/ml (Probability of prostate cancer ) and 4.44% with values > 20.1 ng / ml (prostate cancer) total PSA, a simultaneous 24.44% of patients had serum levels > 1.1 ng/ml free PSA, it was identified that the age group 56-63 years is the most affected with serum free PSA > 1.1 ng/ml with 37.94% (11 patients) and the 62.07% (18 patients) total serum PSA about 4.1-10.0 ng/ml nonspecific diagnosed with prostate disease, 6.90% (2 patients) with serum 10.1-20.0 ng/ml with probability of prostate cancer and 6.90% (2 patients) with serum > 20.1 ng/ml predictive value for prostate cancer and for the type of prostate disorder 16.67% likely to develop benign disorder and 30% for malignant alteration data set by the percent free/total PSA*100 ratio. The results of this investigation must be corroborated through specialized tests and radiological and histopathological studies. Keywords: Prostate Specific Antigen, prostate disorders, Free PSA, Total PSA.